Dispensa coletiva: necessária procedimentalização - Teixeira, Katia Albuquerque Ferreira (2013)
This work has the purpose to study the collective dismissal in Brazil and present guidelines for their regulation. Firstly, we conducted a historical study on the employment relationship protection; following it an assessment on how the collective dismissal occurs in Brazil to demonstrate its harmful effects due to the absence of specific legislation. Describes itself about the ways to solve conflicts in collective dismissal to defend that negotiation is the first and the best way to resolve them. Foreign legislation is also analysed and contributes to substantiate the general assumptions of the regulation proposal . In an evolutionary line, yet are presented summaries of the main trial between 2008 and 2009 that culminated in the premises fixed by the Labour Superior Tribunal (TST) to determinate the previous collective negotiation before the collective dismissal In the end, are presented the guidelines for the additional legislation that will regulate article 7, item I, of the Federal Constitution specifically as regards the collective dismissal and that will provide for the minimum elements for their achievement and discipline, procedures regarding consultation, information, or communications, in addition to deploying the necessary collective bargaining and delimit the consequences for noncompliance